CAADP BR data improvements and challenges: A critical analysis of theme 2 in the 3rd BR cycle - Benin, Samuel; Navarro, Dorian; Laborde Debucquet, David; Fynn, Mark; Makhura, Moraka; Moletsane, Atang; Adama, David; Kimathi, Sally; Kaliba, Matildah (International Food Policy Research Institute, 2022)
To improve the quality of data and reporting for the fourth cycle of the Comprehensive Africa Agriculture Development Programme (CAADP) Biennial Review (BR),1 the African Union (AU) conducted a critical analysis of the process, data, and reporting associated with the third BR. Improving the quality of the BR data will increase the reliability of policy implications derived from rigorous analysis of the data, which may in turn encourage policymakers to implement the resulting recommendations to accelerate agricultural transformation and achieve the goals and targets of the Malabo Declaration. This note summarizes the critical analysis conducted by the technical working group for Theme 2 (TWG2) on enhancing investment finance in agriculture.2 The analysis is based on review of the BR technical documents, evaluation of the processes for data collection and management, and a check of data consistency, including analysis of outliers, illogical or implausible values, and discrepancies with other publicly available datasets. Preliminary findings of the analysis were discussed at several meetings with stakeholders interested in the theme. The results and recommendations were presented at a general meeting organized by the AU with all the TWGs and stakeholders on August 1–5, 2022, in Yaoundé, Cameroon. This note will be useful for the AU and its technical partners for developing standards and guidelines for conducting uniform critical analyses across the various BR technical working groups.